Development of Hardware for Smart Flood Warning System - Bong, Xi Nian; Mohd Fadly Abd Razak (Progress in Engineering Application and Technology, 2024)
Flooding is a common natural disaster that can cause significant damage to property, infrastructure, and human life. In flood-prone areas, it is critical to have an effective flood warning system that can provide real-time data on the water levels, rainfall intensity, and water flow rates to predict potential floods accurately. Existing flood warning systems often suffer from limitations such as delayed warnings, insufficient data accuracy, and limited coverage. These shortcomings result in inadequate response times, hindering effective evacuation, infrastructure protection, and resource allocation. This research aims to develop a hardware for flood monitoring system which automatically collects and processes the real time data of flood monitoring. Beside that, to obtain the information from sensors through calibrations and comparing to the actual manual measurement.